Review of Vasileios Syros’s, Marsilius of Padua at the Intersection of Ancient and Medieval Traditions of Political Thought - Tounta, Eleni (Historein, 2014)
Review of: Vasileios Syros, Marsilius of Padua at the Intersection of Ancient and Medieval Traditions of Political Thought, Toronto: University of Toronto Press, 2012, pp. x + 305